Tabletting forming method and application of dimethyl ether carbonylation catalyst

The sheet-like catalyst prepared by the tablet forming process solves the problems of uneven loading and uneven pressure drop caused by uneven catalyst particles in the traditional extrusion molding process, and achieves higher loading density and reactor stability.

CN119793519APending Publication Date: 2025-04-11YANCHANG ZHONGKE (DALIAN) ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411722234.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The catalyst prepared by the traditional extrusion molding process is uneven in the loading due to uneven particles and uneven pressure drop in the reactor, which affects the reaction effect and catalyst stability.

Method used

The dimethyl ether carbonylation catalyst is prepared by the tablet forming process. By granulating the catalyst powder, sieve it into small particles, and mixing it uniformly with the additive, it is pressed and molded in a proprietary mold to obtain a regular sheet-like catalyst.

Benefits of technology

The catalyst is regular and beautiful, the filling density is large and uniform, which reduces the pressure drop difference between the pipes in the reactor and improves the stability and efficiency of the reactor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005158539160000081
    Figure BDA0005158539160000081
  • Figure BDA0005158539160000082
    Figure BDA0005158539160000082
  • Figure BDA0005158539160000091
    Figure BDA0005158539160000091
Patent Text Reader

Abstract

The invention discloses a dimethyl ether carbonylation catalyst tabletting forming method and application. The forming method at least comprises the following steps: I, granulating catalyst powder, and screening to obtain small-particle catalysts; step II, preparing an auxiliary agent; and step III, uniformly filling the small catalyst particles obtained in the step I and the auxiliary agent obtained in the step II into a special mold, and carrying out compression molding to obtain the flaky catalyst. The invention provides a tabletting forming process which is used for preparing a catalyst and is applied to a tubular reactor, so that the filling quality of the catalyst and the consistency of the reaction effect are remarkably improved, the progress of a catalyst preparation technology in the chemical industry field can be promoted, and the production efficiency and the product quality are improved. Therefore, the method has wide application prospect and market value in industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for tabletting a dimethyl ether carbonylation catalyst and its application, belonging to the field of chemical technology. Background Art

[0002] The catalyst prepared by the traditional extrusion molding process has uneven particle diameter and length due to process conditions. Therefore, there is a tendency for loose and solid particles to be staggered during the filling process, and even for channeling and uneven pressure drop to occur in the tubular reactor. These problems affect the reaction effect and the stability of the catalyst. Although the extrusion molding process has high production efficiency, the catalyst particles are unevenly arranged, resulting in uneven pressure drop and inconsistent reaction effect when the fluid in the reactor flows in the channel.

[0003] CN 106890670 B discloses a catalyst for producing methyl acetate by carbonylation of dimethyl ether. The fixed bed catalyst particles obtained by extrusion molding of the catalyst have poor uniformity and are prone to channeling and uneven pressure drop in the reactor. CN 115591574 A discloses a porous alumina-supported metal copper catalyst, which is obtained by kneading and extruding with alumina. Although the dimethyl ether conversion rate of this scheme is high and the methyl acetate selectivity is good, in the actual industrial production process, the pressure drop generated by the catalyst in the reactor is uneven and the reaction effect consistency is poor. In this regard, the present application provides a method for tableting a dimethyl ether carbonylation catalyst. Summary of the invention

[0004] According to one aspect of the present application, a method for tabletting a dimethyl ether carbonylation catalyst is provided, the tabletting method comprising at least the following steps:

[0005] Step I: granulating the catalyst powder and screening it into small particle catalyst;

[0006] Step II: preparing an auxiliary agent;

[0007] Step III: The catalyst particles obtained in step I and the additives obtained in step II are uniformly mixed and loaded into a proprietary mold, and pressed into shape to obtain a flake catalyst.

[0008] Optionally, the molecular sieve powder is selected from at least one of a modified EMT molecular sieve catalyst, a metal-doped MOR molecular sieve catalyst, a non-metal modified molecular sieve catalyst, and a zeolite catalyst.

[0009] Optionally, the metal in the metal-doped MOR molecular sieve catalyst is selected from at least one of Fe, Al, Cu, Ce, Ca and Mg.

[0010] Optionally, the granulation is selected from at least one of tableting granulation, dry granulation and melt granulation.

[0011] Optionally, the small particle catalyst is 20 to 100 meshes.

[0012] Optionally, the pressing pressure is 0.1 to 300 kN;

[0013] Optionally, the pressing pressure is independently selected from any value among 0.1 kN, 0.2 kN, 0.4 kN, 0.8 kN, 1.6 kN, 3.2 kN, 6.4 kN, 12.8 kN, 25.6 kN, 51.2 kN, 102.4 kN, 204.8 kN, 300.0 kN or a range between any two of the above points.

[0014] The pressing time is 0.01s to 60s.

[0015] Optionally, the pressing time is independently selected from any value among 0.01s, 0.02s, 0.04s, 0.08s, 0.16s, 0.32s, 0.64s, 1.28s, 25.6s, 51.2s, 60.0s or a range between any two of the above points.

[0016] Optionally, the diameter of the sheet catalyst is 2.5 to 5.5 mm.

[0017] Optionally, the diameter of the sheet catalyst is independently selected from any value among 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, or a range between any two of the above points.

[0018] Optionally, the length of the sheet catalyst is 2.5 to 8.6 mm.

[0019] Optionally, the length of the sheet catalyst is independently selected from any value of 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, 7.0 mm, 7.5 mm, 8.0 mm, 8.5 mm, 8.6 mm, or a range between any two of the above points.

[0020] Optionally, the sheet catalyst has a strength of 120 to 330 N / cm.

[0021] Optionally, the strength of the sheet catalyst is independently selected from any value among 120N / cm, 130N / cm, 140N / cm, 150N / cm, 160N / cm, 170N / cm, 180N / cm, 190N / cm, 200N / cm, 210N / cm, 220N / cm, 230N / cm, 240N / cm, 250N / cm, 260N / cm, 270N / cm, 280N / cm, 290N / cm, 300N / cm, 310N / cm, 320N / cm, 330N / cm, or a range between any two of the above points.

[0022] According to another aspect of the present application, an application of a tablet-shaped dimethyl ether carbonylation catalyst is provided, wherein dimethyl ether and a raw gas containing carbon monoxide are introduced into a tubular reactor, contacted with the tablet catalyst, and reacted to obtain methyl acetate.

[0023] Optionally, the reaction conditions are as follows:

[0024] The reaction temperature is 100-240°C;

[0025] The reaction pressure is 1-10 MPa.

[0026] Optionally, the bulk density of the sheet catalyst is 0.6-0.75 kg / L.

[0027] Optionally, the bulk density of the flake catalyst is independently selected from any value among 0.60kg / L, 0.61kg / L, 0.62kg / L, 0.63kg / L, 0.64kg / L, 0.65kg / L, 0.66kg / L, 0.67kg / L, 0.68kg / L, 0.69kg / L, 0.70kg / L, 0.71kg / L, 0.72kg / L, 0.73kg / L, 0.74kg / L, 0.75kg / L, or a range between any two of the above points.

[0028] Optionally, the volume space velocity of dimethyl ether is 1800 to 15000 h -1 .

[0029] Optionally, the volume space velocity of dimethyl ether is independently selected from 1800h -1 , 2400h -1 、3000h -1 、3600h -1 , 4200h -1 、4800h -1 , 5400h -1 、6000h -1 、6600h -1 , 7200h -1、7800h -1 , 8400h -1 , 9000h -1 , 9600h -1 , 10200h -1 , 10800h -1 、14000h -1 , 14600h -1 、15000h -1 Any value in or a range of values ​​between any two of the above points.

[0030] Optionally, in the raw gas, the molar ratio of carbon monoxide to dimethyl ether is 0.1:1 to 20:1.

[0031] Optionally, in the raw gas, the molar ratio of carbon monoxide to dimethyl ether is independently selected from any value among 0.1:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1 or a range value between any two of the above points.

[0032] Optionally, the feed gas comprises carbon monoxide.

[0033] Optionally, the raw gas also includes at least one of hydrogen, nitrogen, argon and methane.

[0034] Optionally, the volume content of carbon monoxide in the raw gas is 10 to 100%.

[0035] The beneficial effects of this application include:

[0036] 1) The catalyst obtained in the present application is neat and beautiful: the catalyst presents a neat and beautiful appearance, which improves its packing quality and visual effect.

[0037] 2) The catalyst packing density obtained in the present application is large and uniform: the tableting process can achieve a higher catalyst packing density and a more uniform density distribution.

[0038] 3) The catalyst obtained in the present application makes the pressure drop of each tube in the shell-and-tube reactor consistent: the pressure drop difference between the pipes in the shell-and-tube reactor is reduced, and the stability and efficiency of the reactor are improved. DETAILED DESCRIPTION

[0039] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0040] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels. The analysis methods in the examples of this application are as follows:

[0041] The mechanical strength of the catalyst was measured using a ZQL-II intelligent particle strength testing machine;

[0042] The products were analyzed using an Agilent 7890 gas chromatograph.

[0043] The conversion rate of dimethyl ether and the selectivity of methyl acetate in the examples of the present application are calculated as follows:

[0044] In the examples of the present application, the conversion rate of dimethyl ether and the selectivity of methyl acetate are calculated based on the carbon molar number of dimethyl ether:

[0045] Dimethyl ether conversion rate = [(moles of dimethyl ether carbon in the feed gas) - (moles of dimethyl ether carbon in the product)] ÷ (moles of dimethyl ether carbon in the feed gas) × (100%)

[0046] Methyl acetate selectivity = (2 / 3) × (the number of moles of carbon of methyl acetate in the product) ÷ [(the number of moles of carbon of dimethyl ether in the feed gas) - (the number of moles of carbon of dimethyl ether in the product)] × (100%).

[0047] Comparative Example 1

[0048] 0.42 g of ferric nitrate nonahydrate was dissolved in 20.00 g of water, and then 0.33 g of oxalic acid dihydrate was added, and the mixture was stirred at room temperature for 10 min to obtain a solution I containing complexed iron ions; 0.34 g of sodium aluminate was dissolved in 19.00 g of water, and the mixture was stirred at room temperature for 10 min to obtain a solution II; solution I and solution II were added dropwise to 11.32 g of industrial grade water glass (modulus 3.3, 26 wt% SiO2, 8 wt% Na2O, 66 wt% H2O, i.e., mass fraction 34%) to obtain a solution III, and magnetic stirring was performed to obtain a synthetic gel, the magnetic stirring speed was 400 r / min, and the mixture was stirred for 4 h; the synthetic gel was transferred to a reactor, and crystallized at 180° C. for 24 h under static conditions to obtain a paste product; the mixture was filtered and washed until the pH value was about 7, and dried at 105° C. for 12 h to obtain a solid powder product.

[0049] The obtained solid powder is put into an extruder, extruded into strips through a strip-shaped orifice plate, and then cut into strips by a cutting device to obtain strip samples.

[0050] Then the strip sample was placed in a 1 mol / L ammonium chloride solution, and ion exchange was performed at 80°C according to a solid-liquid ratio of 1:10 g / mL, and repeated 3 times. After drying, it was calcined at 550°C in an air atmosphere for 4 hours to obtain a MOR molecular sieve doped with metallic iron in situ, which was recorded as catalyst DB1#.

[0051] Example 1

[0052] 0.42 g of ferric nitrate nonahydrate was dissolved in 20.00 g of water, and then 0.33 g of oxalic acid dihydrate was added, and the mixture was stirred at room temperature for 10 min to obtain a solution I containing complexed iron ions; 0.34 g of sodium aluminate was dissolved in 19.00 g of water, and the mixture was stirred at room temperature for 10 min to obtain a solution II; solution I and solution II were added dropwise to 11.32 g of industrial grade water glass (modulus 3.3, 26 wt% SiO2, 8 wt% Na2O, 66 wt% H2O, i.e., mass fraction 34%) to obtain a solution III, and magnetic stirring was performed to obtain a synthetic gel, the magnetic stirring speed was 400 r / min, and the mixture was stirred for 4 h; the synthetic gel was transferred to a reactor, and crystallized at 180° C. for 24 h under static conditions to obtain a paste product; the mixture was filtered and washed until the pH value was about 7, and dried at 105° C. for 12 h to obtain a solid powder product.

[0053] The obtained solid powder sample was then placed in a 1 mol / L ammonium chloride solution, and ion exchange was carried out at 80°C with a solid-liquid ratio of 1:10 g / mL, which was repeated three times. After drying, it was calcined at 550°C in an air atmosphere for 4 h to obtain a MOR molecular sieve in situ doped with metallic iron.

[0054] Take 50g of the synthesized MOR molecular sieve catalyst, add 15g of kaolin, 1g of sesbania powder and 50g of dilute nitric acid (5%), and then put the material into an extruder to extrude into strips, and then crush and granulate in a pulverizer, and sieve into 20-100 mesh small particle catalysts. The small particle catalyst is placed in a special tableting mold with an inner diameter of 5mm, and pressed at a pressure of 20kN for 2s to obtain a sheet catalyst, which is recorded as catalyst 1#. The diameter, length, strength and bulk density of the catalyst are shown in Table 1.

[0055] Example 2

[0056] The catalyst was prepared according to the method described in Example 1, except that the catalyst was pressed for 1 second under a mold pressure of 50 kN to obtain a sheet catalyst, recorded as catalyst 2#. The diameter, length, strength and bulk density of the catalyst are shown in Table 1.

[0057] Example 3

[0058] The catalyst was prepared according to the method described in Example 1, except that the dilute acid was replaced with 50 g of dilute phosphoric acid (5%) to obtain a sheet catalyst, recorded as catalyst 3#. The diameter, length, strength and bulk density of the catalyst are shown in Table 1.

[0059] Example 4

[0060] The catalyst was prepared according to the method described in Example 1, except that 50 g of the synthesized MOR molecular sieve catalyst was added with 15 g of silica sol and 1 g of methyl cellulose, and then 0.5 g of fatty alcohol polyoxyethylene ether and 35 g of dilute phosphoric acid (5%) were added and mixed, and then the material was placed in a mold for compression molding, and then crushed and granulated in a pulverizer, and sieved into 20-100 mesh small particle catalysts. The small particle catalyst was placed in a special tableting mold with an inner diameter of 5 mm, and pressed at a pressure of 15 kN for 2 seconds to obtain a sheet catalyst, which was recorded as catalyst 4#. The diameter, length, strength and bulk density of the catalyst are shown in Table 1.

[0061] Comparative Example 2

[0062] According to the method in the literature Synthesis of silica-rich faujasite using crown-ethers asemplates F.Delprato et, ZEOLITES, 1990, VOl 10: 546, an EMT molecular sieve with a silicon-aluminum ratio of 4.2 was prepared. By water vapor dealumination at 600°C for 1 hour, 2 hours, 4 hours, and 8 hours, EMT molecular sieves with silicon-aluminum atomic ratios (Si / Al) of 10, 15, 20, and 30 were obtained, and EMT molecular sieves with silicon-aluminum ratios of Si / Al=10, Si / Al=15, Si / Al=20, and Si / Al=30 were used for catalyst preparation, respectively, and recorded as 2-1#, 2-2#, 2-3#, and 2-4#, respectively.

[0063] Samples 2-1#, 2-2#, 2-3#, and 2-4# were placed in the extruder respectively, extruded into strips through a strip orifice plate, and then cut into strips by a cutting device to obtain strip samples 2-11#, 2-22#, 2-33#, and 2-44#.

[0064] Then, samples 2-11#, 2-22#, 2-33#, and 2-44# were placed in 1 mol / L ammonium chloride solution, and ion exchange was carried out at 80°C according to a solid-liquid ratio of 1:10 g / mL. This was repeated 3 times. After drying, they were calcined at 550°C in an air atmosphere for 4 h to obtain DB21#, DB22#, DB23#, and DB24# catalysts. The diameter, length, strength, and bulk density of the catalysts are shown in Table 1.

[0065] Example 5

[0066] According to the method in the literature Synthesis of silica-rich faujasite using crown-ethers asemplates F.Delprato et, ZEOLITES, 1990, VOl 10: 546, an EMT molecular sieve with a silicon-aluminum ratio of 4.2 was prepared. By water vapor dealumination at 600°C for 1 hour, 2 hours, 4 hours, and 8 hours, EMT molecular sieves with silicon-aluminum atomic ratios (Si / Al) of 10, 15, 20, and 30 were obtained, and EMT molecular sieves with silicon-aluminum ratios of Si / Al=10, Si / Al=15, Si / Al=20, and Si / Al=30 were used for catalyst preparation, respectively, and recorded as 2-10#, 2-20#, 2-30#, and 2-40#, respectively.

[0067] Then, samples 2-10#, 2-20#, 2-30#, and 2-40# were placed in 1 mol / L ammonium chloride solution, and ion exchange was carried out at 80°C with a solid-liquid ratio of 1:10 g / mL. This was repeated three times. After drying, they were calcined at 550°C in an air atmosphere for 4 h to obtain samples 2-10q#, 2-20q#, 2-30q#, and 2-40q#.

[0068] Take 50g of sample 2-10q#, add 15g of kaolin, 1g of sesbania powder and 50g of dilute nitric acid (5%), put the material into an extruder, extrude into strips, and then crush and granulate in a pulverizer, and sieve into 20-100 mesh small particle catalysts. The small particle catalyst is placed in a special tableting mold with an inner diameter of 5mm, and pressed for 2s under a pressure of 60kN to obtain a sheet catalyst, which is recorded as catalyst 5#. The diameter, length, strength and bulk density of the catalyst are shown in Table 1.

[0069] Example 6

[0070] The catalyst was prepared according to the method described in Example 5, except that 50 g of sample 2-20q# was added, 15 g of kaolin, 1 g of sesbania powder and 50 g of dilute phosphoric acid (5%) were mixed, and the material was placed in an extruder to be extruded into strips, and then crushed and granulated in a pulverizer, and sieved into small particle catalysts of 20-100 mesh. The small particle catalyst was placed in a special tableting mold with an inner diameter of 5 mm, and pressed at a pressure of 70 kN for 2s to obtain a sheet catalyst, which was recorded as catalyst 6#. The diameter, length, strength and bulk density of the catalyst are shown in Table 1.

[0071] Example 7

[0072] The catalyst was prepared according to the method described in Example 5, except that 50 g of sample 2-30q# was added, 15 g of silica sol, 1 g of methyl cellulose and 50 g of dilute nitric acid (5%) were mixed, and the material was placed in an extruder to be extruded into strips, and then crushed and granulated in a pulverizer, and sieved into small particle catalysts of 20-100 meshes. The small particle catalyst was placed in a special tableting mold with an inner diameter of 5 mm, and pressed at a pressure of 80 kN for 1 s to obtain a sheet catalyst, which was recorded as catalyst 7#. The diameter, length, strength and bulk density of the catalyst are shown in Table 1.

[0073] Example 8

[0074] The catalyst was prepared according to the method described in Example 5, except that 50 g of sample 2-40q# was added, 15 g of silica sol, 1 g of methyl cellulose and 50 g of dilute nitric acid (5%) were mixed, and the material was placed in an extruder to be extruded into strips, and then crushed and granulated in a pulverizer, and sieved into 20-100 mesh small particle catalysts. The small particle catalyst was placed in a special tableting mold with an inner diameter of 5 mm, and pressed at a pressure of 40 kN for 2 seconds to obtain a sheet catalyst, which was recorded as catalyst 8#. The diameter, length, strength and bulk density of the catalyst are shown in Table 1.

[0075] Table 1 Test Example 1

[0076]

[0077] The catalysts obtained in Examples 1 to 8 and Comparative Examples 1 to 2 were loaded into a fixed bed reactor to perform the carbonylation of dimethyl ether to produce methyl acetate. The initial activity of the catalyst was investigated under standard evaluation conditions, with a reaction temperature of 188°C, a pressure of 2.0 MPa, a raw gas composition of DME:CO:H2=1:10:9, and a feed space velocity of GHSV=1800 h -1 , the test results are shown in Table 2.

[0078] Table 2

[0079]

[0080]

[0081] Test Example 2

[0082] The catalysts obtained in Examples 1 to 8 and Comparative Examples 1 to 2 were loaded into a fixed bed reactor to perform carbonylation of dimethyl ether to produce methyl acetate. The catalyst life was investigated under severe evaluation conditions. The reaction temperature was 208° C., the pressure was 2.0 MPa, the raw gas composition was DME:CO:H2=1:10:9, and the feed space velocity was GHSV=14400 h -1 , the test results are shown in Table 3.

[0083] Table 3

[0084] Conversion rate of dimethyl ether (%) Methyl acetate selectivity (wt%) Comparative Example 1 40.06 96.80 Example 1 59.37 98.45 Example 2 60.28 98.98 Example 3 60.12 99.05 Example 4 61.98 98.59 Comparative Example 2-DB21# 42.00 98.00 Comparative Example 2-DB22# 49.08 97.99 Comparative Example 2-DB23# 51.30 98.56 Comparative Example 2-DB24# 50.09 98.07 Example 5 60.03 98.58 Example 6 62.65 98.66 Example 7 63.79 99.01 Example 8 62.03 99.64

[0085] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for tabletting a dimethyl ether carbonylation catalyst, characterized in that: The molding method comprises at least the following steps: Step I: granulating the catalyst powder and screening it into small particle catalyst; Step II: preparing an auxiliary agent; Step III: The catalyst particles obtained in step I and the additives obtained in step II are uniformly mixed and loaded into a proprietary mold, and pressed into shape to obtain a flake catalyst.

2. The method according to claim 1, characterized in that The molecular sieve powder is selected from at least one of a modified EMT molecular sieve catalyst, a metal-doped MOR molecular sieve catalyst, a non-metal modified molecular sieve catalyst, and a zeolite catalyst; Preferably, the metal doped MOR molecular sieve catalyst comprises at least one metal selected from Fe, Al, Cu, Ce, Ca and Mg; The granulation is selected from at least one of tablet granulation, dry granulation, extrusion granulation or spray granulation; The small particle catalyst is 20 to 100 meshes.

3. The method according to claim 1, characterized in that The method for preparing the auxiliary agent comprises combining at least one of paraffin powder, sodium stearate, magnesium stearate, cellulose, starch, methyl cellulose, microcrystalline cellulose, sesbania powder, ethylene glycol powder, graphene and graphite.

4. The method according to claim 1, characterized in that The pressing pressure is 0.1 to 300 kN; The pressing time is 0.01s to 60s.

5. The method according to claim 1, characterized in that The diameter of the sheet catalyst is 0.5 to 15 mm; Preferably, the length of the sheet catalyst is 2.5 to 8.6 mm.

6. The method according to claim 1, characterized in that The sheet catalyst has a strength of 120 to 330 N / cm.

7. An application of a tablet-formed dimethyl ether carbonylation catalyst, characterized in that: Dimethyl ether and raw gas are introduced into a tubular reactor, contacted with a flake catalyst, and reacted to obtain methyl acetate; The sheet catalyst is prepared by any one of the methods of claims 1 to 6.

8. The use according to claim 7, characterized in that: The reaction conditions are as follows: The reaction temperature is 100-240°C; The reaction pressure is 1-10 MPa; Preferably, the bulk density of the sheet catalyst is 0.6 to 0.75 kg / L; Preferably, the volume space velocity of dimethyl ether is 1800 to 15000 h -1 ; In the raw gas, the molar ratio of carbon monoxide to dimethyl ether is 0.1:1 to 20:

1.

9. The use according to claim 7, characterized in that: The raw gas includes carbon monoxide; Preferably, the raw gas also includes at least one of hydrogen, nitrogen, argon and methane.

10. The use according to claim 7, characterized in that: The volume content of carbon monoxide in the raw gas is 10-100%.

Citation Information

Patent Citations

  • A catalyst for the carbonylation of dimethyl ether to produce methyl acetate and its application.

    CN106890670B

  • Porous alumina supported metal copper catalyst and preparation method thereof

    CN115591574A